THE EFFECT OF TRANSFORMATIONAL LEADERSHIP AND ORGANIZATIONAL COMMITMENT ON EMPLOYEE JOB SATISFACTION WITH WORK MOTIVATION AS A MEDIATION VARIABLE IN THE MINISTRY OF POPULATION AND FAMILY DEVELOPMENT, SOUTH SULAWESI PROVINCE - Raihan Nugrah Wardana Anwar; Romansyah Sahabuddin; Muhammad Ichwan Musa; Widhi Nugraha Sumiharja Darmawinata (Jurnal Manajemen, 2026)
Abstract: This study aims to analyze the influence of transformational leadership and organizational commitment on employee job satisfaction with work motivation as a mediating variable in employees of the Ministry of Population and Family Development of South Sulawesi Province. This study uses a quantitative approach with a survey method. The study population was all 95 employees with a saturated sampling technique so that the entire population was used as a research sample. Data were collected through questionnaires using a five-point Likert scale and analyzed using the Partial Least Squares-Structural Equation Modeling (PLS-SEM) method with the help of SmartPLS 4.0 software. The analysis included descriptive statistics, measurement model tests (outer model) consisting of validity and reliability tests, and structural model tests (inner model) to examine the relationship between variables. The test results showed that all constructs met the validity and reliability criteria with Cronbach's alpha values above 0.90 and composite reliability above the required limit. The results of the structural analysis showed that transformational leadership and organizational commitment had a positive and significant effect on work motivation and job satisfaction. The coefficient of determination indicates that employee job satisfaction can be explained by 0.739 transformational leadership, organizational commitment, and work motivation, while work motivation can be explained by 0.468 transformational leadership and organizational commitment. These findings indicate that increasing employee job satisfaction requires the implementation of effective transformational leadership, strengthening organizational commitment, and continuously increasing work motivation within the organization.Keywords: Transformational Leadership, Organizational Commitment, Work Motivation, Job Satisfaction